2004
DOI: 10.1007/s00401-004-0911-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of multiple promoter-associated CpG islands in meningiomas: relationship with the allelic status at 1p and 22q

Abstract: The purpose of this research was to examine the DNA methylation profile of meningiomas. Accordingly, we examined the DNA methylation status of ten tumor-related genes (RB1, p16(INK4a), p73, MGMT, ER, DAPK, TIMP-3, p14(ARF), THBS1, and Caspase-8) in 98 meningiomas (68 grade I; 27 grade II; and 3 grade III samples) using methylation-specific PCR and sequencing. The most frequently methylated genes were THBS1 (30%), TIMP-3 (24%), p16(INK4a) (17%), MGMT (16%), p73 (15%), ER (15%), and p14(ARF) (13%), whereas methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
3
62
0
2
Order By: Relevance
“…In these neoplasms, immunohistochemical analysis showed that loss of TIMP3 expression is especially frequent in tumours with poor differentiation (38). In meningiomas, no hypermethylation of the TIMP3 promoter has been detected (39) and no aberrant gene methylation of this gene has been reported (40). The silencing of the TIMP3 gene or its deletion, as it is located in a genomic region, 22q12, that is frequently deleted in meningioma (41), might be involved in the progression of this neoplasm.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In these neoplasms, immunohistochemical analysis showed that loss of TIMP3 expression is especially frequent in tumours with poor differentiation (38). In meningiomas, no hypermethylation of the TIMP3 promoter has been detected (39) and no aberrant gene methylation of this gene has been reported (40). The silencing of the TIMP3 gene or its deletion, as it is located in a genomic region, 22q12, that is frequently deleted in meningioma (41), might be involved in the progression of this neoplasm.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Aberrant methylation of the promoter represents an alternative epigenetic change to the genetic mechanisms, leading to tumor suppressor gene inactivation. Methylation of specific subsets of CpG islands has been proposed to be associated with specific tumor types (Esteller et al, 2001;Bello et al, 2004). Hypermethylation of promoters usually occurs at CpG islands.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of data in the existing literature on the status of MGMT methylation of meningiomas. Bello et al (Bello et al, 2004) detected aberrant MGMT methylation in 13%,26%, and 0% of grade I,II and III tumors. In another study Yanli liu et al (2005) reported the status of aberrant MGMT methylation in 6% ( 1/16) of grade I,5% (1/19) of grade II, and 8%(1/13) of grade III tumors.…”
Section: Discussionmentioning
confidence: 98%
“…The modified DNA was amplified using primers specific for either methylated or unmethylated MGMT promoter sequences. The primers were used in earlier reports (Bello et al, 2004) and are listed in Table 1.…”
Section: Bisulfite Treatmentmentioning
confidence: 99%